Booster-free anti-retroviral therapy for persons living with HIV and multidrug resistance (B-Free): protocol for a multicentre, multistage, randomised, controlled, non-inferiority trial - Nathalie Schwab; Andreas Limacher; Felix Rintelen; Gilles Wandeler; Marc van der Valk; Marie Ballif; Alexandra Calmy; Marcel Stoeckle; Isabelle Peytremann-Bridevaux; Sofia C. Zambrano; Fabrice Bonnet; Matthias Cavassini; et al. (BMJ Open)
Introduction Anti-retroviral therapy (ART) simplification strategies are needed for treatment-experienced people with HIV (PWH) and multidrug-resistant viruses. These individuals are commonly treated with boosted ART regimens and are thereby at risk for harmful drug-drug interactions (DDI). In this trial, we aim to assess the efficacy of the combination doravirine, dolutegravir and lamivudine (DOR/DTG/3TC) among people with a history of virological failure who receive boosted ART.Methods and analysis B-Free is a multistage, randomised, multicentre, open-label, non-inferiority trial, embedded within the Swiss HIV Cohort Study and conducted in collaboration with cohorts of PWH in the Netherlands and France. Cohort participants with a history of ART change due to virologic failure and who maintain HIV virologic suppression with an ART regimen consisting of a pharmacological booster and at least two drugs from classes other than nucleoside reverse transcriptase inhibitors are included. Patients with major drug resistance mutations against DTG or DOR and individuals with chronic hepatitis B virus infection are not eligible for the study. Individuals are randomised 1:1 to either receiving co-formulated DTG/3TC and DOR once daily or continuing their boosted ART regimen. The primary outcome is the proportion of individuals lacking virologic control (HIV-RNA ≥50 cp/mL) at 48 weeks, according to the Food and Drug Administration snapshot algorithm. Changes in DDI burden (assessed using a DDI score), treatment satisfaction (assessed using the HIV Treatment Satisfaction Questionnaire), quality of life and mental health represent key secondary outcomes. Additional secondary outcomes include the proportion of individuals developing new resistance-associated mutations and changes in quality of life and mental health. In a qualitative substudy, we will conduct semistructured interviews with a subset of participants to assess their expectations and experiences towards HIV treatment and clinical research in general. Enrolling 210 individuals will provide 80% power to demonstrate non-inferiority, defined as less than 8% absolute increase in loss of viral suppression in individuals randomised to DOR/DTG/3TC (one-sided type I error rate of 0.025).Ethics and dissemination The study was approved by the competent ethics committees (reference number BASEC 2023–01060) and the regulatory authority Swissmedic (reference number 701655) in Switzerland before the enrolment of the first participant. Approval by the European Medicines Agency and local ethical committees in the Netherlands and France will be obtained prior to including participants in these countries. Participant’s written informed consent is obtained by the investigators before enrolment. The results of all major B-Free study outcomes will be submitted to peer-reviewed journals that enable Open Access publication.Trial registration number Swiss National Clinical Trials Portal (SNCTP000005686, registered on 06 November 2023) and Clinicaltrials.gov (NCT06037564, registered on 07 September 2023).